Ergonomic improvement through job rotations in repetitive manual tasks in case of limited specialization and differentiated ergonomic requirements. Issue 12 (2016) - Boenzi, F.; Digiesi, S.; Facchini, F.; Mummolo, G.
Abstract: Despite increasing automation in modern manufacturing industry, human labor still represents an irreplaceable element in many operations which require variety and flexibility, particularly in the case of assembly operations. Concurrently, the majority of developed countries, both European and Asian, has to face the problem of workforce aging. Ergonomic issues are therefore gaining an ever increasing attention by plant managers, given the strict link among productivity, healthy status of aged workers and lost working hours or working days due to ergonomic-related injuries. Technological constraints and productivity requirements often represent the main drivers at the design stage of production systems. Even when ergonomic constraints have been considered, in the production phase different problems, requiring immediate interventions, could emerge, for example in reference to age differences among workers. In these situations, organizational changes can be very effective and job rotation of operators is largely utilized. In the present paper, the OCRA (Occupational Repetitive Action)-score method is adopted for the ergonomic assessment in case of infrequent job rotations. An algorithm which, implementing different ergonomic criteria, identifies, among all the feasible job rotations, the best solutions in presence of a sub-group of operators requiring lower risk exposure is illustrated. A case study from the automotive industry shows an example of its application.